African Conflict and Peacebuilding Review (JSTOR)
African Conflict and Peacebuilding Review (ACPR) is an interdisciplinary forum for creative and rigorous studies of conflict and peace in Africa, and for discussions among scholars, practitioners, and public intellectuals in Africa, the United States, and other parts of the world. ACPR provides a wide range of theoretical, methodological, and empirical perspectives on the causes of conflicts and peace processes including, among others, cultural practices relating to conflict resolution and peacebuilding, legal and political preventative measures, and the intersection of international, regional, and local interests and conceptions with conflict and peace. ACPR is a joint publication of the Africa Peace and Conflict Network, the West African Research Association, and Indiana University Press.
Keywords: African Studies